The use of theoretical and empirical knowledge in the production of explanations and arguments in an inquiry biology activity - Maíra Batistoni e Silva; Sílvia Luzia Frateschi Trivelato (Investigações em Ensino de Ciências, 2017)
Agreeing with the scientific literacy as the purpose of science education and with the recent propositions that in order to achieve it we should favor the engagement of students in practices of scientific culture, this study intends to analyze the production of explanations and arguments in an inquiry based teaching activity in order to characterize students' mobilization of theoretical and empirical knowledge by engaging in these practices. Analyzing the scientific reports elaborated by the students (14-15 years old) after the inquiry activity on population dynamics, we highlight the importance of empirical knowledge about the experimental context as a repertoire for construction of explanations, especially when students deal with anomalous data. This knowledge was also important for production of valid arguments, since most of the justifications were empirical, regardless of whether or not the data were in accordance with the explanatory model already known. These results reinforce the importance of students' engagement in inquiry activities, as already defended by different authors of this research area, and indicate that the inquiry practice allowed the engagement in epistemic practices, since the knowledge about the experimental conditions and the procedures of data collection provided a repertoire for the production of explanations and arguments. Finally, we discuss the relevance of this research to the field of biology teaching, seeking to defend the promotion of inquiry activities with an experimental approach as an opportunity to integrate conceptual and epistemic objectives and overcome the difficulties generated by the specificities of this area of knowledge in relation to the other disciplines in nature sciences.